(untitled) (Revista Contexto & Saúde, 2025)
The objective is to understand the impact of urinary incontinence on the quality of life of older adults. This is a qualitative, descriptive-exploratory study conducted with eleven older adults affected by UI, belonging to the Family Health Strategy of a municipality located in the far west region of Santa Catarina. Data collection took place in August 2021 through individual semi-structured interviews. Data analysis was performed using thematic content analysis. From the analysis, one thematic category emerged: Discourses and experiences of older adults with urinary incontinence and its impact on their quality of life. It is evident that urinary incontinence negatively affects the quality of life of older adults, mainly in the psychological and social domains. The triggered feelings are verbalized as shame due to odor, frustration at the risk of being seen in public with wet clothes, fear, anxiety, insecurity, and sadness. When compounded, such sensations increase the likelihood of psychological disorders, which are responsible for the development of depressive conditions, low self-esteem, withdrawal from leisure activities, and, overall, contribute to social isolation. Based on the study, it is clear that there is a need to increase the visibility of the problem, highlighting the influence of qualified listening that can bring improvements not only to the physical problems arising from urinary incontinence, but also – and especially – to the biopsychosocial and spiritual dimensions of the individual.